Absorption Resonance Energy Transfer between Organic Dyes (Cumarin and Rohdamain ) - Wajeha Abdle Diam (Journal of Global Pharma Technology, 2016)
The spectral properties absorption of two laser dyes types, C480 and R610, the mixture was investigated. These types  of laser dyes  belong to Coumarinoids  and  Xanthenes  family were dissolved  using  ethanol  as solvent to prepare samples with range of ratios (1:1,  1:2,  1:3 and 1:4)  from  Cumarin  480 (C48) to Rohdamin 610 (R610) concentered in (10-410-5,10-6) M/L at room temperature. The achieved results pointed out an increase in the absorption intensities with the increasing of the concentration of the day type R610 from 10-6 and 10-5 to 10-4   M/L.the same thing for C480which are absorved in agreement with Beer-Lambert law and the finished results Pointed that  the absorption peak was moved toward the short wavelengths (BLUE SHIFT) when increasing the ratioconcentration.  Keywords: Dye laser, Fluorescence resonance energy transfer, Silica gel matrices. Absorption spectrum.